Analisis Pengaruh Perceived Organizational Support Terhadap Affective Commitment Melalui Kepuasan Kerja - SHOLEKAH, (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine and analyze the effect of perceived organizational support on affective commitment through job satisfaction as an intervening variable in PT. PLN (Persero) UIT JBTB UPT Surabaya. This research is a type of quantitative research with a permanent employee population of PT. PLN (Persero) UIT JBTB UPT Surabaya and sampling using saturated sampling techniques with a sample of 49 employees. The statistical analysis used in this study is Partial Least Square (PLS) with the help of software SmartPLS 3. The results of this study indicate that perceived organizational support has a significant positive effect on affective commitment, perceived organizational support has a significant positive effect on job satisfaction, job satisfaction has no significant and positive effect on affective commitment. Keywords: affective commitment; job satisfaction; perceived organizational support;.